Nanobiosensor de estrés - Hernández Garcés, Paulina (Universidad Autónoma Metropolitana, 2015)
The fundamental principle for possible design of a stress nanobiosensor is overstated in this work. The objective was to understand and develop a sensor with low cost, high efficiently, simple use and maintenance, to give big accessibility for common population. It is assumed that sensor no requires special skill or special equipment; it’s dedicated to personal use. In this thesis several models of stress nanobiosensor were designed and developed. All are based on detection of cortisol (hydrocortisone) in saliva samples. Developed sensors measured changes in color or fluorescence in presence of artificial saliva (model solution) and samples of human saliva. In total, 5 different types of sensors were investigated and each one show different characteristics, disadvantages for the future development, which is detail described in thesis. The stress nanobiosensor named “ojo de búho (ODB)” whit nano-ELISA «sándwich» setup shows the best characteristics in terms of high sensitivity, high efficiency and high stability. This particular sensor was evaluated in function of different concentration of cortisol and different reaction time. Since the design of such sensor is based on recent advantage and knowledge of nanobiotechnology, it’s surface was characterized by AFM at the nanometric level. The obtain results clearly emphasize the special roll of AuNP on formation of nanostructure film, which is crucial for sensor functionality. Finally a set of results of stress evaluation done by our sensor for samples taken from six different are presented. Significant difference and satisfactory response was observed when it was evaluated in 6 different human subjects.; Durante la realización del presente proyecto, se desarrollaron los principios fundamentales para la generación de un Nanobiosensor de Estrés, para uso domestico, en principio de recientes avances en Nanobiotecnología. La meta fue entender el mejor camino para desarrollar un sensor de bajo costo, alta eficiencia, manejo simple y gran accesibilidad en términos de costo/producción. Se desarrollo un Nanobiosensor de estrés en papel, con un diseño específico, se investigaron 5 caminos para la detección de cortisol (hidrocortisona) en muestras de saliva artificial, que presentaran características ópticas (visuales): cambio color y fluorescencia. Los Nanobiosensores, fueron evaluados con saliva artificial y con muestras de saliva humana. Cada opción investigada (diseño, modelo) mostro ventajas y desventajas para el desarrollo futuro, detalles presentados en la tesis. El Nanobiosensor de estrés denominado en la tesis como «ojos de búho (ODB)» con nano-ELISA «sándwich» mostro las mejores características, con una alta sensitividad, alta eficiencia y gran estabilidad. El sensor fue evaluado en función de diferentes concentraciones de hidrocortisona y diferentes tiempos de respuesta. Su superficie se evaluó en diferentes fases de las modificaciones con un análisis AFM a nivel nanométrico, el cual claramente muestra la reestructuración de la superficie del sensor por presencia de AuNP. Finalmente una serie de sensores, fueron evaluados con saliva de diferentes sujetos, presentando notable diferencia y satisfactoria respuesta.